Compliance with Chinese characteristics : evaluating China's compliance record with regard to WTO-related liberalization commitments in the life insurance sector - Shields, Justin M. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Political Science ))--University of Stellenbosch, 2006.